Temporal Study of TSS (Total Suspended Solid) Around Porong River Estuary Due To the Influence of Lapindo Mud Based On Landsat 8 OLI Satellite Imagery - Mubarok, Ihsan Dwi; Rifardi, Rifardi; Tanjung, Afrizal (Jurnal Perikanan dan Kelautan, 2019)
This research was conducted in April 2019 to determined TSS concentrations using Landsat 8 OLI Satellite imagery and of to the coefficient TSS concentrations at period of before and after Lapindo mudflow event using Landsat 8 OLI satellite imagery in Porong River estuary Sidoarjo Regency East Java Province. TSS from 25 sampling points with 3 replication were taken from the estuary. The result showed that fluctuation of TSS occured around Porong River estuary before and after Lapindo mudflow event from 2000-2019. Algoritm of Budhiman (2004) got the best result for analyst TSS concentration around Porong River estuary. The highest concentration was in estuary. In 2008, the concentration in estuary was 216,07 mg/l. (R2 =0,915 ; r = 0,957). The Development of Algoritm of Budhiman (2004) produced formula of TSS (mg/l) = -6.7625 + (1.2129 * (8.1429 * (Exp (23.704 * 0.94 * Band-Red))))